ANALISA PENERAPAN ETIKA PROFESI DALAM PELAYANAN SEKTOR PUBLIK DI SATBRIMOB: Studi Kasus pada Satbrimob Polda Jatim - Marwa, Lailatul; Kuswardijah, Sugi (Ekomania, 2023)
The quality of public sector services is a demand that is expected by the community. The quality of public services is also a form of the totality of services carried out by the State apparatus to the fulles, in accordance with the rules and procedures that have been stipulated in accordance with the legislation so that it can meet the satisfaction, needs, and expectations of the community as service recipients. In this study, the aim is to analyze professional ethics in public sector services at the Brimob Unit of the East Java Police. Another goal is to find out the application of professional ethics in government agencies, especially in the Satbrimob Polda Jatim. The method used in this research is to use a descriptive method, which collects some data and quotes and summarizes various situations from various data collected in the form of interviews or observations about the problem being studied. Primary legal materials and secondary legal materials are methods of data collection. Then the data obtained is processed using qualitative research methods in order to obtain more specific information about the problem to be studied, utilize sources of information related to relevant theories and collect information related to the theme raised. The results of research related to the implementation of professional ethics in public sector services have been stipulated in Law number 14 of 2011 concerning the Police Professional Code of Ethics and National Police Chief Regulation Number 19 of 2012 concerning the Police Code of Ethics commission, so that this provision applies to all members of the National Police. According to researchers within the scope of Satbrimob, they have applied professional ethics, especially in public sector services in carrying out their duties. But there are also obstacles so that the service is not fast and precise due to the lack of human resources in terms of adequate young personnel.